Survey of copyright officers in the UK 2017-2018 - Hatch, Philippa (UK Data Service, 2018)
Survey data providing information about copyright officers or similar specialists in UK libraries, educational and cultural institutions and also details of the training they provide. The responses have been anonymised to allow sharing for research purposes. Questions about this survey should be addressed to copyrightlitgmail.com.